Nitric Acid Oxidized ZrO2 as the Tunneling Oxide of Cobalt Silicide Nanocrystal Memory Devices - Hu, Chih-Wei; Chang, Ting-Chang; Tu, Chun-Hao; Chen, Yang-Dong; Lin, Chao-Cheng; Chen, Min-Chen; Lin, Jian-Yang; Sze, Simon M.; Tseng, Tseung-Yuen (My University, 2011)
In this study, ZrO2 formed by the nitric acid oxidation method is proposed to be the tunneling oxide for nonvolatile memory device applications. The sputtered Zr thin film was oxidized by immersing in the nitric acid solution (HNO3:H2O = 1:10) for 60 s at room temperature. The quality of the formed ZrO2 was also extracted by the capacitance-voltage and current density-voltage measurements. Then, X-ray photoelectron spectroscopy has been used to confirm that the deposited Zr can be oxidized completely after the oxidation process. Moreover, a CoSi2 thin film was deposited on the nitric acid oxidized ZrO2 as the self-assembled layer of the memory device. After the device fabrication, the electrical and material characteristics of the CoSi2 nanocrystal memory devices have also been demonstrated and discussed.
Keywords: Cobalt silicide; nanocrystal; nitric acid oxidation; nonvolatile memory; ZrO2